Environmental impacts of shrimp aquaculture: the case of Chandipur village at Debhata upazila of Satkhira district, Bangladesh (Journal of the Asiatic Society of Bangladesh, Science, 2014)
The present study based on primary investigations (focus group discussion, field observation, household interviews etc.), laboratory analysis for soil and water quality (heavy metal test, pH, salinity, electricity conductivity, particle size analysis etc.) and secondary materials (remote sensing data, satellite images analysis etc.) reveals that due to poor drainage system and continuous shrimp farming at Chandipur Village under Debhata Upazila of Satkhira District, salinity level of both soil and water are increasing (1.6 ppt and 13.4 ppt respectively). In addition PH, salinity, electrical conductivity of soil and water have been found in a very fragile condition. Different types of heavy and toxic metals such as Na, Fe, Cr, Zn, Ni and Pd have been detected in ghers soil.J. Asiat. Soc. Bangladesh, Sci. 40(1): 107-119, June 2014